The girls in the picture [compact disc, unabridged] : a novel - Benjamin, Melanie, 1962- (Random House Audio, 2018)
In 1914, Frances Marion finds her calling writing screenplays, and in a friendship with actress Mary Pickford. But the two women's ambitions are challenged by limitations imposed on their gender, and their astronomical success could come at a price.